PENGARUH BERBAGAI JENIS PUPUK ORGANIK PADA PANJANG STEK YANG BERBEDA TERHADAP PERTUMBUHAN BIBIT BUAH NAGA ( Hylocereus costaricensis) - Kesuma, Komang Alit Giri; Ete, Andi; Noer, Hamid (AGROTEKBIS, 2017)
This study aims to determine the effect of various types of organic fertilizers and various cuttings of different length 0n the growth of dragon fruit seedlings. Research was carried out in Green House of Faculty of Agriculture, University Tadulako, in April to June 2015. This study used a randomized block design (RBD) with factorial pattern of two factors. The first factor was the length of cuttings (S) consisting of three (3) sizes: S1 = 20 cm, S2 = 25 cm, and S3 = 30 cm. Then the second factor was the application of various types of manure (P) consisting of four (4) treatments, namely: Pa = Control, Pb = chickenmanure, 50 g / polybag, Pc = goatsmanure, 50 g / polybag, and Pd = beefmanure, 50 g / polybag. Based on these two factors, then it obtained 12 combination treatments and it was repeated 3 times, and each treatment consisted of two polybags, so there were 72 experimental units. Data were analyzed by analysis of variance (F test), at the level of 95% or Î± 0.5. When the real effect of treatment will be continued by real difference test honestly (HSD) Î± 0.5.Â Key Words: Dragon Fruit Seeds Growth, Length Cuttings, and Organic Fertilizer Type,